1998
DOI: 10.1097/00004647-199802000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Increased Formation of Reactive Oxygen Species after Permanent and Reversible Middle Cerebral Artery Occlusion in the Rat

Abstract: In barbiturate-anesthetized rats, we induced 3 hours of permanent middle cerebral artery occlusion (MCAO) by an intraluminal thread (n = 6), or 1 hour MCAO followed by 2 hours of reperfusion (n = 6). Through a closed cranial window over the parietal cortex, the production of reactive oxygen species (ROS) was measured in the infarct border using online in vivo chemiluminescence (CL) while monitoring the appearance of peri-infarct depolarizations (PID). The borderzone localization of the ROS and direct current (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
170
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(183 citation statements)
references
References 42 publications
10
170
0
3
Order By: Relevance
“…10) However, AGE-positive cells were observed at 5 days after skull vibration, and edaravone administration reduced the number of AGE-positive cells through its radical-scavenging activity. Based on our previous report that skull vibration reduced cerebral surface blood flow in rats under the same experimental conditions as in this study, as well as a report that the amount of free radicals in the brain increased after experimental cerebral ischemiareperfusion, 12) we speculate that skull vibration under the present experimental conditions reduced cerebral blood flow, and reperfusion led to the production of free radicals.…”
Section: Discussionsupporting
confidence: 82%
“…10) However, AGE-positive cells were observed at 5 days after skull vibration, and edaravone administration reduced the number of AGE-positive cells through its radical-scavenging activity. Based on our previous report that skull vibration reduced cerebral surface blood flow in rats under the same experimental conditions as in this study, as well as a report that the amount of free radicals in the brain increased after experimental cerebral ischemiareperfusion, 12) we speculate that skull vibration under the present experimental conditions reduced cerebral blood flow, and reperfusion led to the production of free radicals.…”
Section: Discussionsupporting
confidence: 82%
“…Neutrophil influx occurs in the first 24 h after ischemia followed by monocyte migration from 24 h up to 5 days (Hallenbeck et al, 1986;Danton and Dietrich, 2003). The inflammatory response involves rolling, firm adhesion and transendothelial migration of leukocytes on the level of postcapillary venules, BBB dysfunction and increased production of proinflammatory mediators including reactive oxygen species, nitric oxide, cytokines, adhesion molecules and chemokines (Peters et al, 1998;Schuerer et al, 1994;Lindauer et al, 1996;Okada et al, 1994;Che et al, 2001;Yang et al, 1999). All of these mediators have been suggested as being involved in BBB 'breakdown' during inflammation, causing a dysfunction of TJ structure (abnormality in occludin and ZO-1), greater influx of blood-borne cells and further amplification of inflammation and brain parenchymal damage (Plumb et al, 2002;Gloor et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, free radical production in the penumbral zone increases during both events (Liu et al, 2003). Despite the low oxygen tension produced during ischemia, exist an increase in ROS formation after 1.6 h of ischemia, the highest ROS production (489 ± 330% of control) occurs after 20 min of reperfusion, and remains increased at least for 3 h (Peters et al, 1998). Christensen et al (1994) reported that ROS production is maximal during the first hour of reperfusion.…”
Section: Ischemiamentioning
confidence: 97%
“…As previously described, physiopathological mechanisms leading to neuronal injury in cerebral stroke are complex and multifactorial. However, several studies suggest that oxidative stress, secondary to ROS and RNS production, actively participates during postischemic brain damage (Peters et al, 1998;Rodrigo et al, 2005). During ischemia, free radical production in the infarct zone decreases or remains without change, while it increases during reperfusion.…”
Section: Ischemiamentioning
confidence: 99%